Peningkatan Kedisiplinan Siswa pada Nilai-Nilai Keagamaan Penerapan dengan Manajemen Pembiasaan Pagi - Dita Maulidia Putri Utami; Denok Mugi Hidayanti; Jhoni Susanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Al-Furqan Jember Junior High School students receive assistance in one of the work programs that is carried out regularly, namely morning habituation. The goal is to develop character in discipline and behavior of students. During the implementation of the morning habituation program, this assistance is carried out routinely through observation and documentation methods. The results of this activity can be used as a good bridge to form a disciplined and responsible personality, as well as making students have a sense of courtesy and can respect their teachers and friends.